2017
DOI: 10.3748/wjg.v23.i37.6788
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical perspectives on irritable bowel syndrome in India, Bangladesh and Malaysia: A review

Abstract: Irritable bowel syndrome (IBS) is a chronic gastrointestinal disorder, common in clinic and in the community. It has a significant impact on both society and patients’ quality of life. The epidemiology, clinical presentation, and management of IBS may vary in different geographical regions due to differences in diet, gastrointestinal infection, socio-cultural and psycho-social factors, religious and illness beliefs, symptom perception and reporting. Although previous reviews and consensus reports on IBS in Asi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 93 publications
(121 reference statements)
4
47
0
Order By: Relevance
“…In both the Manning and Asian criteria, "abdominal pain or discomfort" were not included as an absolute requirement for the diagnosis of IBS, which resulted in their greater frequency for diagnosing IBS in the Indian population. 8 Similar findings have been reported in other Asian populations. In a Hong Kong study, 68.0% of patients with IBS reported bloating, compared to only 32.0% who complained of abdominal pain.…”
Section: Symptom Presentation and Diagnostic Issuessupporting
confidence: 81%
See 3 more Smart Citations
“…In both the Manning and Asian criteria, "abdominal pain or discomfort" were not included as an absolute requirement for the diagnosis of IBS, which resulted in their greater frequency for diagnosing IBS in the Indian population. 8 Similar findings have been reported in other Asian populations. In a Hong Kong study, 68.0% of patients with IBS reported bloating, compared to only 32.0% who complained of abdominal pain.…”
Section: Symptom Presentation and Diagnostic Issuessupporting
confidence: 81%
“…33 Furthermore, more fiber results in a greater stool weight, which additionally reduces colonic transit time. In the light of the differences in dietary fiber intake, Rahman et al 8 additionally showed that the mean intestinal transit time among Northern Indian adults was 39.9 hours compared to 83.4 hours in Caucasian adults (Fig. 1).…”
Section: Lifestyle and Cultural Habitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of acute gastroenteritis in the tropics including India and Bangladesh is high [66]. On the other hand, in most of the studies, the prevalence of IBS among the general adult population in India and Bangladesh has been found to be between 4% and 8% [67], which is lower compared with the global prevalence of 11.2% [68]. The reason for the low prevalence of IBS in spite of the high prevalence of acute gastroenteritis in these countries remains enigmatic.…”
Section: Incidence Of Pi-ibs and Its Relationship With The Hygiene Hymentioning
confidence: 96%